Functional movement asymmetries have limited association with physical performance improvements following a youth athlete conditioning program - Parsons, J. L.; Preston, S. (Journal of Australian Strength and Conditioning, 2020)
Training programs based on the Long-Term Athlete Development (LTAD) model ideally incorporate activities that optimise physical performance and create resilient athletes through promotion of movement competency and neuromuscular control. However, limited evidence exists regarding the relationship between movement control and physical performance. This study examined physical performance and movement control in adolescent athletes after participation in a 3-month training program and explored whether movement asymmetry predicts changes in physical performance. Twenty-five healthy athletes (16 female, 9 male; 14.6 ± 1.2 years of age) registered in a University youth athletic development program participated. Before and after the training program, athletes completed tests of physical performance [10 & 20 m sprints, countermovement jump (CMJ), Reactive Strength Index (RSI)] and movement control [Y-Balance test (YBT), Functional Movement Screen (FMS)]. Twenty metre sprint time (pre- 3.43 ± 0.20; post-test 3.39 ± 0.18 seconds, p=0.02), CMJ height (pre- 27.5 ± 4.4; post-test 29.5 ± 5.6 cm, p=0.002), and RSI (pre- 1.04 ± 0.42; post-test 1.20 ± 0.31, p=0.02) improved, but no change was observed in any of the movement control variables. Fewer FMS subtest asymmetries predicted greater improvement in jump height, however, YBT asymmetry, sex, and years to age of peak height velocity were not related to any of the significant improvements in performance. A youth training program, delivered 2-3x/week, improved sprint speed, jump height, and reactive strength, but did not affect movement control. Programs should perhaps consider inclusion of activities that target movement control more specifically. Movement control, as measured by YBT and FMS asymmetry, had limited influence on improvements in physical performance in youth athletes; the use of alternative measures in future studies may prove more successful.